1998
DOI: 10.1103/physreve.58.4361
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium fluctuations in time-dependent diffusion processes

Abstract: A fluctuating hydrodynamics approach is presented for the calculation of the structure factor for timedependent nonequilibrium diffusive processes in binary liquid mixtures. The hydrodynamic equations are linearized around the time-dependent macroscopic state given by the usual phenomenological diffusion equation. The cases of free diffusion, thermal diffusion, and barodiffusion are considered in detail. The results are used to describe the low-angle scattered intensity distributions from the time-dependent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
180
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(188 citation statements)
references
References 19 publications
8
180
0
Order By: Relevance
“…Further theoretical [7] and experimental [8] investigation showed that on Earth, the scale invariance of the fluctuations is broken by the force of gravity, which stabilizes long-wavelength fluctuations and thus prevents their divergence. The same gravitational stabilization of the fluctuations was shown to be present during timedependent isothermal diffusion processes [9][10][11][12], proving that nonequilibrium fluctuations are a general feature of diffusive processes, irrespective of the origin of the concentration gradient driving them. An additional mechanism breaking the scale invariance of the fluctuations at small wave vectors was predicted theoretically to be the finite size of the sample [13], a finding confirmed experimentally during the GRADFLEX experiment by the European Space Agency [14][15][16].…”
Section: Introductionmentioning
confidence: 93%
“…Further theoretical [7] and experimental [8] investigation showed that on Earth, the scale invariance of the fluctuations is broken by the force of gravity, which stabilizes long-wavelength fluctuations and thus prevents their divergence. The same gravitational stabilization of the fluctuations was shown to be present during timedependent isothermal diffusion processes [9][10][11][12], proving that nonequilibrium fluctuations are a general feature of diffusive processes, irrespective of the origin of the concentration gradient driving them. An additional mechanism breaking the scale invariance of the fluctuations at small wave vectors was predicted theoretically to be the finite size of the sample [13], a finding confirmed experimentally during the GRADFLEX experiment by the European Space Agency [14][15][16].…”
Section: Introductionmentioning
confidence: 93%
“…Under non-equilibrium conditions, the gradient of one variable couples the spontaneous fluctuations of the velocity of the fluid molecules with the fluctuations of the relevant variable, thus providing a huge enhancement of the intensity of the fluctuations, increasing with their size. This phenomenon has been widely investigated in the latest decades and a sound theoretical description (see for example [59][60][61][62][63]) as well as many experimental studies [46,47,49,[64][65][66][67] can be found in the literature. Here, we would like to recall the essential equations that describe the intensity of the light scattered by concentration fluctuations generated in a fluid out of equilibrium and in the presence of the terrestrial gravitational field.…”
Section: Non-equilibrium Fluctuationsmentioning
confidence: 99%
“…60,61 Careful experiments have demonstrated that diffusion, especially for a system near a critical solution point, can be affected by gravitational acceleration. [62][63][64][65][66][67] We are currently studying both the IBA-water and 1-butanolwater systems by laser line deflection 52 to determine how the diffusion under 1 g compares to what is seen in the tensiometer.…”
Section: Figure 10mentioning
confidence: 99%